Algorithmics - David Harel (Addison-Wesley, 1992)
The book tells a story concerning the concepts, ideas, methods, and results fundamental to computer science. It introduces the basic ideas of algorithms, including their structures and methods of data manipulation. It then examines how to design accurate, efficient algorithms and discusses their inherent limitation